2022
DOI: 10.3390/socsci11020051
|View full text |Cite
|
Sign up to set email alerts
|

Still Mother after All These Years: Infants Still Prefer Mothers over Fathers (If They Have the Choice)

Abstract: Fathering and mothering have changed in many ways within the last decades. Earlier studies showed a clear hierarchy in infant attachment figures with a preference for mothers. This study examined whether infants in the 21st century still prefer mothers over fathers in their expression of attachment behaviors, whether differences in parental involvement still exist, and whether this will result in differences in attachment security to mother and father. A total of 50 German families with infants between 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…The results also revealed that AQS attachment security to mother and father is moderately positively correlated similar as reported in other studies [86,91]. Moreover, AQS dependency to mother and father showed an even higher positive association, suggesting that AQS dependency might be a characteristic of the child and no relationship specific characteristic [38].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results also revealed that AQS attachment security to mother and father is moderately positively correlated similar as reported in other studies [86,91]. Moreover, AQS dependency to mother and father showed an even higher positive association, suggesting that AQS dependency might be a characteristic of the child and no relationship specific characteristic [38].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, attachment security and dependency seem to be slightly more independent in child-father than in child-mother relationships. This would somehow support the idea that attachment to mother is characterized by a higher frequency of closer emotional interactions, whereas child-father attachment is characterized by more challenging interactions and more autonomy support [85,86]. However, this also…”
Section: Discussionmentioning
confidence: 54%
“…Attachment researchers are increasingly aware of the importance of attachment to father and that attachment to father could add important insights to the study of the associations between attachment and children’s developmental outcomes (e.g., Deneault et al, 2021; Dagan & Sagi-Schwartz, 2018). The current study’s focus on attachment towards mother makes sense as maternal attachment appears a stronger predictor of children’s mental health than paternal attachment (e.g., ZImmermann et al, 2022), but other research suggests that the conjoint inclusion of attachment to both parents does provide a more nuanced understanding of links between attachment and mental health outcomes (Rivers et al, 2022). So, including attachment towards father in attachment -EC research could be a valuable avenue for future research.…”
Section: Discussionmentioning
confidence: 94%
“…The gender difference may be accounted for by the variations in the levels of social and emotional connections of children with their parents during the advanced years. Compared to fathers, children tend to form deeper emotional relationships with their mothers ( Lewis & Lamb, 2003 ; Portu-Zapirain, 2013 ; Zimmermann et al, 2022 ). These close ties put mothers in a better position to benefit more from children’s assistance.…”
Section: Discussionmentioning
confidence: 99%